2020
DOI: 10.1002/adom.202001702
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrolled Light‐Harvesting Supramolecular Assembly Based on Aggregation‐Induced Excimer Emission

Abstract: should be relatively high. [9] Considering the advantages of host-guest interaction, supramolecular assembly with macrocycle has turned out to be a useful approach to develop aqueous light-harvesting systems. [10] For example, Tang and co-workers reported an efficient light-harvesting system with ultrahigh antenna effect based on aggregation-induced enhanced emission (AEE) conjugated polymeric supramolecular network. [11] Anderson and co-workers synthesized a complex comprising a cyanine dye rotaxane and a por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 47 publications
(18 reference statements)
1
35
0
Order By: Relevance
“…Based on aggregation-induced excimer emissions, DAE derivatives and CD can also participate in the construction of photocontrolled light-harvesting supramolecular assemblies that exhibit broad-spectrum multicolor photoluminescence, with DAE providing the basis for light controllability. Liu et al [100] assembled polyanionic γ-CD, a pyrene derivative (PYC12), Nile red, and a DAE derivative into nanoparticles in an aqueous solution. The polyanionic γ-CD significantly promoted the aggregation-induced excimer emission properties of the PYC12 and a high-efficiency (up to 83%) energy transfer process from the PYC12 to the Nile red.…”
Section: Host-guest Complexes Based On Daementioning
confidence: 99%
See 2 more Smart Citations
“…Based on aggregation-induced excimer emissions, DAE derivatives and CD can also participate in the construction of photocontrolled light-harvesting supramolecular assemblies that exhibit broad-spectrum multicolor photoluminescence, with DAE providing the basis for light controllability. Liu et al [100] assembled polyanionic γ-CD, a pyrene derivative (PYC12), Nile red, and a DAE derivative into nanoparticles in an aqueous solution. The polyanionic γ-CD significantly promoted the aggregation-induced excimer emission properties of the PYC12 and a high-efficiency (up to 83%) energy transfer process from the PYC12 to the Nile red.…”
Section: Host-guest Complexes Based On Daementioning
confidence: 99%
“…[186] DAE units can be loaded within an energy donor/acceptor assembly, which allows the energy transfer process to be controlled through the reversible photoisomerization of DAE and thereby provides an effective method for regulating the emission characteristics of the supramolecular assembly. Liu et al [100] reported a multicolor, tunable, luminescent, supramolecular light-harvesting assembly formed by the self-assembly of polyanionic γ-cyclodextrin (COONaγ-CD), a pyrene derivative (denoted as PYC12 in the original text), Nile red, and a DAE derivative in an aqueous solution. Pyrene derivatives exhibit aggregation-induced excimer emission enhancement.…”
Section: Changes In Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Sustained by [π•••π] interactions, hydrogen bonding, hydrophobic forces, electrostatic interactions, and/or other noncovalent bonding interactions, the superstructures associated with these assemblies can be modulated, giving rise to tunable photophysical properties. [39,40] Moreover, in contrast with emission in the solution state, emission in the solid state-especially in the crystalline state-is highly dependent on the noncovalent bonding interactions between molecules and their geometrical arrangements with respect to each other. Consequently, altering the molecular arrangement in the crystalline state serves as an alternative approach to tuning solid-state luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…The components of the chosen dyad (carbazole derivative and pyrene) were selected because they play a pivotal role in many areas of photophysics and optoelectronics. These popular polycyclic aromatic hydrocarbons and their various derivatives (including silicon-based carbazole , and pyrene-containing compounds ) have found application in optoelectronics, solar cells, TADF and organic light-emitting diode (OLED) materials, or fluorescent probes for elucidation of the geometries of various biomolecules. , There are also interesting studies that report white-light emission from pyrene-based compounds, and many of them are related to aggregation-induced emission. Furthermore, there are known examples of carbazole–pyrene hybrid compounds for dye-sensitized solar cell applications, OLEDs, and electroluminescent devices …”
Section: Introductionmentioning
confidence: 99%